2018
DOI: 10.1002/nbm.4027
|View full text |Cite
|
Sign up to set email alerts
|

Fitting algorithms and baseline correction influence the results of non‐invasive in vivo quantitation of 2‐hydroxyglutarate with 1H‐MRS

Abstract: 1H‐MRS enables non‐invasive detection of 2‐hydroxyglutarate (2‐HG), an oncometabolite accumulating in gliomas carrying mutations in the isocitrate dehydrogenase (IDH) genes. Reliable 2‐HG quantitation requires reproducible post‐processing, deployment of fitting algorithms and quantitation methods. We prospectively enrolled 38 patients with suspected or recently diagnosed gliomas (IDH mutated n = 26). The MRI protocol included a 1H single voxel PRESS sequence with volumes of usually 8 mL or more (20 × 20 × 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Longer echo times (significant increased sensitivity and specificity in TE 97 ms compared to TE 30-35 ms) [30], ultra-high-field MRI (7T) [31,32], 2D correlation spectroscopy (COSY) at 3T [33] and 2D L-COSY at 7T [34] were used to improve detection of the 2-HG signal. Different post-processing techniques have also been applied in various settings, mostly in a limited number of patients (e.g., 38 patients in Reference [35]). Interestingly, independent of 2-HG, peak alterations of other metabolites were frequently seen (e.g., Cho, Glu, Gly, glutathione, cystathionine [36][37][38]) and sometimes used to improve detection of IDH mutation status, for example, combination of 2-HG and Glu levels [39] The described techniques are frequently not suitable for clinical routine as they need extensive technical and personal capacities [24].…”
Section: Discussionmentioning
confidence: 99%
“…Longer echo times (significant increased sensitivity and specificity in TE 97 ms compared to TE 30-35 ms) [30], ultra-high-field MRI (7T) [31,32], 2D correlation spectroscopy (COSY) at 3T [33] and 2D L-COSY at 7T [34] were used to improve detection of the 2-HG signal. Different post-processing techniques have also been applied in various settings, mostly in a limited number of patients (e.g., 38 patients in Reference [35]). Interestingly, independent of 2-HG, peak alterations of other metabolites were frequently seen (e.g., Cho, Glu, Gly, glutathione, cystathionine [36][37][38]) and sometimes used to improve detection of IDH mutation status, for example, combination of 2-HG and Glu levels [39] The described techniques are frequently not suitable for clinical routine as they need extensive technical and personal capacities [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our study benefited from the use of a high field 14.1 T animal scanner, which allowed us to distinguish the different metabolites and probe their modulation with treatment. In the clinical setting MR scanners are typically at the lower fields of 1.5 T or 3 T. However, as mentioned above, sequences specifically optimized to probe for 2-HG and Glu or GLX have been developed and can be used to monitor the metabolic changes associated with treatment [23,26,32,41,42]. Thus, our observations are also relevant to the clinical setting.…”
Section: Discussionmentioning
confidence: 97%
“…In order to understand the substantial variability introduced by the choice of analysis tool, the influence of modelling strategies and parameters on quantitative results needs to be better understood. Previous investigations have shown that, within a given LCM algorithm, metabolite estimates can be affected by the choice of baseline knot spacing 37,38 , the modelling of MM and lipids 37,39, and SNR and linewidth 4043 . In this study, we focused on the comparison of each LCM with their default and commonly used parameters, and observed differences resulting both from the default parameters and from differences in the core algorithm.…”
Section: Discussionmentioning
confidence: 99%